Evaluation of the Economic Performances of the European Union Countries and Turkey in the Covid-19 Process with the COPRAS Method - Halil Kete; Fatih Karasaç (İktisat Politikası Araştırmaları Dergisi)
The COVID-19 pandemic has caused the biggest global economic crisis since the Second World War. The European Union, one of the world’s largest economic and political unions, was also seriously affected by this process. This study examines the impact of the COVID-19 epidemic, which emerged in December 2019 and showed its effect intensely in 2020, on the economic performances of 27 member states of the European Union and Turkey, which is a candidate country for the European Union. The Complex Proportional Assessment (COPRAS) technique was used to measure the economic performance of the countries covered in the study. COPRAS is one of the multi-criteria decision-making methods that aims to make a general ranking from the most desired to the least desired in line with the determined criteria. In the study, countries for economic performance measurement; GDP growth rates, per capita GDP current account balance, budget balance, unemployment rate, EU defined general government debt stock and inflation rate data are used. According to the results of the analysis made with the COPRAS method, Slovenia was the best country in terms of economic performance in the context of the data discussed, followed by Denmark and Germany, respectively. The country with the lowest performance in terms of economic performance was Turkey. Turkey is followed by the Greek part of Southern Cyprus and Greece. It has been observed that inflation and unemployment rates have a quite different structure compared to other countries included in the analysis, as the reason for Turkey’s low performance.